A machine learning framework involving EEG-based functional connectivity to diagnose major depressive disorder (MDD) - Mumtaz, W. (Springer Verlag, 2018)
Major depressive disorder (MDD), a debilitating mental illness, could cause functional disabilities and could become a social problem. An accurate and early diagnosis for depression could become challenging. This paper proposed a machine learning framework involving EEG-derived synchronization likelihood (SL) features as input data for automatic diagnosis of MDD. It was hypothesized that EEG-based SL features could discriminate MDD patients and healthy controls with an acceptable accuracy better than measures such as interhemispheric coherence and mutual information. In this work, classification models such as support vector machine (SVM), logistic regression (LR) and NaÃ¯ve Bayesian (NB) were employed to model relationship between the EEG features and the study groups (MDD patient and healthy controls) and ultimately achieved discrimination of study participants. The results indicated that the classification rates were better than chance. More specifically, the study resulted into SVM classification accuracyÂ =Â 98, sensitivityÂ =Â 99.9, specificityÂ =Â 95 and f-measureÂ =Â 0.97; LR classification accuracyÂ =Â 91.7, sensitivityÂ =Â 86.66, specificityÂ =Â 96.6 and f-measureÂ =Â 0.90; NB classification accuracyÂ =Â 93.6, sensitivityÂ =Â 100, specificityÂ =Â 87.9 and f-measureÂ =Â 0.95. In conclusion, SL could be a promising method for diagnosing depression. The findings could be generalized to develop a robust CAD-based tool that may help for clinical purposes. Â© 2017, International Federation for Medical and Biological Engineering.